2004
DOI: 10.1111/j.1365-2621.2004.tb13358.x
|View full text |Cite
|
Sign up to set email alerts
|

Residual Sulfur Metabolites in Isolated Soy Proteins: Sulfite to Cysteine

Abstract: Mean methanethiol headspace concentrations above aqueous slurries of isolated soy proteins (ISP) increased 17-to 36-fold over the controls with the addition of L-cysteine. Corresponding hydrogen sulfide levels were also greatly increased. Dithiothreitol, sodium sulfite, and glutathione increased headspace methanethiol from aqueous ISPs 23-to 44-fold, 8-to 9-fold, and 5-fold, respectively, but did not elevate hydrogen sulfide. These observations, along with the effects from the addition of dithiothreitol/O-acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 44 publications
4
23
0
Order By: Relevance
“…To our knowledge there is no published work addressing the synthesis of hexanal in ISP; however, in previous research in our laboratory into the effect of various reducing agents on the sulfur-containing odorants in ISP [18], we observed that when 6.5 mM dithiothreitol (DTT) was added to aqueous slurries of commercial ISP there were large increases in headspace hexanal levels compared with the levels in the controls. Monma et al [19] and Kemal et al [20] indicated that soybean LOX-1, LOX-2 and/or LOX-3 activities were inhibited by DTT.…”
Section: Introductionmentioning
confidence: 90%
“…To our knowledge there is no published work addressing the synthesis of hexanal in ISP; however, in previous research in our laboratory into the effect of various reducing agents on the sulfur-containing odorants in ISP [18], we observed that when 6.5 mM dithiothreitol (DTT) was added to aqueous slurries of commercial ISP there were large increases in headspace hexanal levels compared with the levels in the controls. Monma et al [19] and Kemal et al [20] indicated that soybean LOX-1, LOX-2 and/or LOX-3 activities were inhibited by DTT.…”
Section: Introductionmentioning
confidence: 90%
“…50 The ability of this class of enzymes to break C-S linkages appears to be dependent on the bacterial species, as a recent study showed that Lactobacillus casei was able to cleave cysteine but this did not occur in Lactobacillus helveticus. 58,59 Methionine γ-lyase purified from Brevibacterium spp. was shown to cleave L-methionine into ammonia and 2-oxobutyrate but also L-cysteine to ammonia, hydrogen sulphide and pyruvate.…”
Section: Bioconversion Of Cysteinementioning
confidence: 99%
“…The actual sulfite content in ISP slurry might be significantly higher due to release of bound sulfite from cysteine‐S‐sulfonates. The modified Monnier‐Williams method used by Boatright and Stine (2004) is only capable of detecting the free sulfite that exists in dry ISP. Boatright and others (2006) found as much as 43 mg/kg cysteine‐S‐sulfonates in ISP samples but the method employed used extensive enzymatic hydrolysis of the protein prior to HPLC analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In a 250‐mL flask, 100 mL of 20‐mM Tris buffer, pH 7.2 containing 3.6 μM MnCl 2 , and 3.2 mM L‐methionine (or L‐methionine‐methyl‐ 13 C 1 ) were combined with varying levels of sodium sulfite (0 to 250 μM). After mixing for 60 min at 22 °C, 10 mL of the static headspace was withdrawn and analyzed by gas chromatography/mass spectroscopy (GC/MS) as described by Boatright and Stine (2004). For methanethiol, m/z 47 was used and m/z 48 was used for methanethiol‐ 13 C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation